IMPLEMENTASI PENDIDIKAN KARAKTER DALAM EFEKTIFITAS PEMBELAJARAN TAHFIDZ PADA SANTRI PONDOK PESANTREN HAMALATUL QUR’AN JOGOROTO JOMBANG - M Wafiyul Ahdi; M Ulil Absor (CV. KAMPUS AKADEMIK PUBLISING, 2024)
The Indonesian government and people face serious challenges in addressing moral degradation and national character issues. Juvenile delinquency and other crimes have become complex problems with negative impacts on society. The implementation of character education is expected to minimize these phenomena and create a generation with good morals and positive behavior. This study aims to analyze the effectiveness of Tahfidz al-Qur’an learning at Pondok Pesantren Hamalatul Qur’an Jogoroto Jombang, with a focus on character education implementation. The research uses a qualitative approach with data collection techniques including observation, interviews, and documentation. The results show that Tahfidz learning, conducted through habituation and intensive practice, has been effective. The character education based on independence and cultural aspects at this pesantren aligns with government policies and existing educational theories, even though it has not been formalized in the official curriculum. Integrated learning activities in the classroom, dormitory, and pesantren environment have a positive impact on the students' personal development, making them more disciplined and responsible. This research is expected to serve as a reference for the development of character education models in other Islamic educational institutions. The abstract covers essential elements such as objectives, methods, results, and implications of the research, providing a clear and comprehensive overview of the written thesis.